GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

It is currently 07 Aug 2020, 01:30

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If (x-p)^2 - (x-t)^2 / t-p = x-t and

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Intern
Intern
avatar
Status: Hulk
Joined: 17 Jul 2013
Posts: 11
Location: Singapore
Concentration: Entrepreneurship, Finance
Schools: Insead '14 (M)
GMAT 1: 600 Q44 V30
GMAT 2: 650 Q45 V34
GMAT 3: 690 Q49 V34
If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 05 Dec 2013, 19:41
1
5
00:00
A
B
C
D
E

Difficulty:

  35% (medium)

Question Stats:

71% (02:16) correct 29% (02:57) wrong based on 217 sessions

HideShow timer Statistics

If \(\frac{(x-p)^2 - (x-t)^2}{t-p} = x-t\) and \(t\neq{p}\) , then x=

A) p
B) t
C) p-2t
D) t+p
E) t-p

What is the best approach to solve for x?
Most Helpful Community Reply
Verbal Forum Moderator
User avatar
B
Joined: 10 Oct 2012
Posts: 562
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 05 Dec 2013, 20:48
5
1
xhimi wrote:
If \(\frac{(x-p)^2 - (x-t)^2}{t-p} = x-t\) and \(t\neq{p}\) , then x=

A) p
B) t
C) p-2t
D) t+p
E) t-p

What is the best approach to solve for x?


We know that\(a^2-b^2 = (a-b)*(a+b)\)

Thus, \(\frac{(x-p)^2 - (x-t)^2}{t-p} = \frac{(x-p+x-t)*[(x-p)-(x-t)])}{t-p} \to \frac{(2x-p-t)*(t-p)}{t-p}\)

As \(t\neq{p}\) , we can cancel it from both Numerator and Denominator, and we get \(2x-p-t = x-t \to x = p\)

A.
_________________
General Discussion
Veritas Prep GMAT Instructor
User avatar
V
Joined: 16 Oct 2010
Posts: 10793
Location: Pune, India
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 05 Dec 2013, 20:42
3
1
xhimi wrote:
If \(\frac{(x-p)^2 - (x-t)^2}{t-p} = x-t\) and \(t\neq{p}\) , then x=

A) p
B) t
C) p-2t
D) t+p
E) t-p

What is the best approach to solve for x?


I would put values for t and p such that each option gives a different answer. Say, t= 3, p = 1. Every option gives a different answer so when I put these values in the equation, I will get my answer for sure.

\(\frac{(x-1)^2 - (x-3)^2}{3-1} = x-3\)

\(\frac{4x - 8}{3-1} = x-3\)

\(2x - 4 = x - 3\)

x = 1
Only option (A) gives 1 when we put t = 3, p = 1 in the options. So x must be equal to p (which is option (A))

Answer (A)
_________________
Karishma
Veritas Prep GMAT Instructor

Learn more about how Veritas Prep can help you achieve a great GMAT score by checking out their GMAT Prep Options >
Intern
Intern
avatar
Status: Hulk
Joined: 17 Jul 2013
Posts: 11
Location: Singapore
Concentration: Entrepreneurship, Finance
Schools: Insead '14 (M)
GMAT 1: 600 Q44 V30
GMAT 2: 650 Q45 V34
GMAT 3: 690 Q49 V34
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 05 Dec 2013, 20:59
I got lost in the algebraic approach, so thanks for showing both ways Karishma and Mau5
SVP
SVP
User avatar
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1705
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 11 Apr 2014, 00:44
1
\(x^2 - 2xp + p^2 - (x^2 - 2xt + t^2) = xt - xp - t^2 + pt\)

(2x - x) * (t-p) = p * (t-p)

x = p

Answer = A
Manager
Manager
User avatar
Joined: 20 Dec 2013
Posts: 114
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 11 Apr 2014, 01:25
1
xhimi wrote:
If \(\frac{(x-p)^2 - (x-t)^2}{t-p} = x-t\) and \(t\neq{p}\) , then x=

A) p
B) t
C) p-2t
D) t+p
E) t-p

What is the best approach to solve for x?


If t = 3 and p = 2 then

(x - 2)^2 - (x - 3)^2 = (x - 3) (3 - 2)

x^2 + 4 - 4x - x^2 - 9 + 6x = x - 3


2x - 5 = x - 3

x = 2

Hence x = p
_________________
76000 Subscribers, 7 million minutes of learning delivered and 5.6 million video views

Perfect Scores
http://perfectscores.org
http://www.youtube.com/perfectscores
Manager
Manager
avatar
G
Joined: 23 Jul 2019
Posts: 189
GPA: 3.9
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and  [#permalink]

Show Tags

New post 28 Jul 2020, 05:12
Any similar questions?
_________________
Let's get some
GMAT Club Bot
Re: If (x-p)^2 - (x-t)^2 / t-p = x-t and   [#permalink] 28 Jul 2020, 05:12

If (x-p)^2 - (x-t)^2 / t-p = x-t and

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne